Evaluation of Water Resources Exploitation in a Karst Region Using Intrinsic Vulnerability Assessment - Alireza Kavousi; Saman Javadi; Hamid Kardan Moghadam; Ali Mirarabi (Water Harvesting Research, 2018)
Groundwater vulnerability assessment is of crucial importance for land use/cover management. Some methods have been proposed specifically for the karst hydrogeological settings. Among them, COP and PaPRIKa, as two commonly applied recent methods, were adopted for the resource vulnerability assessment of a humid temperate karst region, north of Iran. Comparison of water bacterial content and distribution of vulnerability classes within the catchments for nine springs suggests that PaPRIKa got some higher level of validity, showing more consistency to the catchment properties. Vulnerability class of "very low" was absent in the PaPRIKa map, while the "low", "moderate", "high", and "very high" classes comprised 31.7, 48.7, 12.4, and 7.2 percent of the total region, respectively. Distribution of vulnerability classes within the spring catchments was also surveyed. Importantly, the catchment area of the largest spring, namely Sefidab, which has been supplying drinking water for almost one hundred thousand people in Amlash and Roudsar cities, was predominantly located in the "very high" vulnerability class, enclosing 368 sinkholes. Presence of Escherichia Coli in water emerging from all springs stressed the importance of enforcing strict regulations on the land use planning and conducting required treatments for drinking water supply. Moreover, since infiltration from precipitation and direct-runoff is substantial in the "high", and "very high" vulnerability zones, rainwater and floodwater harvesting may face serious technical challenges there. Hence, intrinsic vulnerability assessment in a karst region can be deserved as a basic criterion for the design of water harvesting systems.